(untitled) (Rassegna di Diritto, Legislazione e Medicina Legale Veterinaria, 2017)
The authors analyze the legislation on the establishment of the Registry of pigs, examine the administrative problems about the application of the Legislative Decree no. 200/2010 and the Dir. 2008/71/EC and compare this legislation with Italian region and provincial laws. The issue concerns the bureaucracy for pigs kept as pets or of affection.